On a CVD-formed carbon nitrogen (C3N) film doped with Cu and Zn. Issue 2 (1st February 2022) - Dante, Roberto C.; Lartundo-Rojas, Luis; Martín-Ramos, Pablo; Chamorro-Posada, Pedro; Rutto, Dario; Dante, Denisse G.; Vázquez-Cabo, José; Rubiños-López, Óscar
Abstract: A carbon nitrogen film was formed by chemical vapor deposition on a brass sheet starting from cyanurate of melamine as a precursor, at a temperature of 600 °C. The film was easily detached, and thoroughly characterized by means of various techniques, including X-ray photoelectron spectroscopy, X-ray diffraction, UV-Vis and infrared spectroscopies, and scanning and transmission microscopy. The material exhibited a layered structure, with many particles of zinc and copper compounds embedded on the surface. The band gap was found to be 2.06 eV, much lower than that of conventional g-C3 N4, with values between 3.0 and 2.7 eV. The formula is close to that of C3 N, also known as bidimensional polyaniline.